Mail Art : An Annotated Bibliography - Held, John Jr.; Bleus, Guy (Metuchen, London : The Scarecrow Press Inc., 1991)
Contents: Three Essays on Mail Art ; Explanatory Notes ; Section 1: Books ; Section 2: Magazines ; Section 3: Newspapers ; Section 4: Catalog Essays ; etc.
Engels
boek